# Y f x x3 for 1 x 2 f x 3x2 2 1 9x4 32 2x3

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x > 0. from part (b), e1/(x+1) < eln(1+1/x) < e1/x , e1/(x+1) < 1 + 1/x < e1/x , ex/(x+1) < (1 + 1/x)x < e; by the Squeezing Theorem, lim (1 + 1/x)x = e. x→+∞ (d) 45. Use the inequality ex/(x+1) < (1 + 1/x)x to get e < (1 + 1/x)x+1 so (1 + 1/x)x < e < (1 + 1/x)x+1 . From Exercise 44(d) e − 1 + 1 50 50 < y (50), and from the graph y (50) < 0.06 0.2 0 100 0 46. F (x) = f (x), thus F (x) has a value at each x in I because f is continuous on I so F is continuous on I because a function that is diﬀerentiable at a point is also continuous at that point CHAPTER 7 SUPPLEMENTARY EXERCISES 5. If the acceleration a = const, then v (t) = at + v0 , s(t) = 1 at2 + v0 t + s0 2 6. (a) Divide the base into n equal subintervals. Above each subinterval choose the lowest and highest points on the curved top. Draw a rectangle above the subinterval going through the lowest point, and another through the highest point. Add the rectangles that go through the lowest points to obtain a lower estimate of the area; add the rectangles through the highest points to obtain an upper estimate of the area. Supplementary Exercises 7 250 (b) (c) (a) 3 11 += 24 4 5 −1 − (e) 8. n = 20: 24.4 cm, 23.1 cm (c) 7. n = 10: 25.0 cm, 22.4 cm not enough information (a) (c) 3 4 =− (a) (b) (c) 10. 35 4 −1 1 dx + (f ) not enough information (b) not enough information 13 1 (d) 4(2) − 3 = 2 2 3 − π (3)2 /4 = 0 u = x2 , du = 2xdx; 1 2 −2 1 − x2 dx = 2(1) + π (1)2 /2 = 2 + π/2 −1 12 (x + 1)3/2 3 1 3 =− 2 2 (d) 5 1 +2= 2 2 not enough information 1 9. (b) −1 − 1 1 2 1 (103/2 − 1) − 9π/4 3 1 − u2 du = 0 1 π (1)2 /4 = π/8 2 y 1 0.8 0.6 0.4 0.2 x 0.2 0.6 1 11. The rectangle with vertices (0, 0), (π, 0), (π, 1) and (0, 1) has area π and is much too large; so is the triangle with vertices (0, 0), (π, 0) and (π, 1) which has area π/2; 1 − π is negative; so the answer is 35π/128. 12. Divide ex + 3 into e2x to get e2x dx = ex + 3 13. ex dx − 3 e2x 3ex = ex − x so ex + 3 e +3 ex dx = ex − 3 ln(ex + 3) + C ex + 3 Since y = ex and y = ln x are inverse functions, their graphs are symmetric with respect to the line y = x; consequently the areas A1 and A3 are equal (see ﬁgure). But A1 + A2 = e, so e y e A1 1 x ln xdx + 1 e dx = A2 + A3 = A2 + A1 = e 1 0 A2 A3 1 14. (a) 1 n n k =1 1 lim n→+∞ n k = n n k =1 n f (x∗ )∆x where f (x) = k k =1 k = n 1 x1/2 dx = 0 2 3 √ e x x, x∗ = k/n, and ∆x = 1/n for 0 ≤ x ≤ 1. Thus k 251 Chapter 7 (b) 1 n n k =1 1 lim n→+∞ n n (c) k =1 n 15. k =1 1 x4 dx = = 0 1 5 n f (x∗ )∆x where f (x) = ex , x∗ = k/n, and ∆x = 1/n for 0 ≤ x ≤ 1. Thus k k k =1 k/n e lim k =1 4 k n k =1 n f (x∗ )∆x where f (x) = x4 , x∗ = k/n, and ∆x = 1/n for 0 ≤ x ≤ 1. Thus k k = ek/n = n n→+∞ n 4 k n n n→+∞ n 1 f (x∗ )∆x = k = lim ex dx = e − 1. 0 k =1 1 is positive and increasing on the interval [1, 2], the left endpoint approximation x 1 overestimates the integral of and the right endpoint approximation underestimates it. x Since f (x) = (a) For n = 5 this becomes 1 1 1 1 1 + + + + < 0.2 1.2 1.4 1.6 1.8 2.0 2 1 1 1 1 1 1 1 dx < 0.2 + + + + x 1.0 1.2 1.4 1.6 1.8 2 (b) 1 dx = ln 2 is x For general n the left endpoint approximation to 1 1 n n k =1 n k =1 n 1 = 1 + (k − 1)/n k =1 n 1 . This yields n+k k =1 1 = n+k−1 1 < n+k 2 1 n−1 k =0 1 and the right endpoint approximation is n+k n−1 1 dx < x k =0 1 which is the desired inequality. n+k 1 1 1 1 = so ≤ 0.1, n ≥ 5 (c) By telescoping, the diﬀerence is − n 2n 2n 2n (d) n ≥ 1, 000 16. The direction ﬁeld is clearly an even function, which means that the solution is even, its derivative is odd. Since sin x is periodic and the direction ﬁeld is not, that eliminates all but x, the solution of which is the family y = x2 /2 + C . 17. (a) n 1 · 2 + 2 · 3 + · · · + n(n + 1) = n k =1 = n−1 (b) k =1 k 9 − n n2 17 lim n→+∞ 2 3 n−1 n 2 (c) = j =1 n−1 1− k =1 3 j= j =1 1 n2 (a) n−1 k= k =1 11 17 9 (n − 1) − 2 · (n − 1)(n) = n n2 2 i=1 1 2i + (2)(3) = 2 2 3 3 i+ n−1 ; n i=1 i=1 1 3 = 2 · (3)(4) + (3)(3) = 21 2 19 (k + 4)(k + 1) k =0 k =1 1 1 1 n(n + 1)(2n + 1) + n(n + 1) = n(n + 1)(n + 2) 6 2 3 14 18. k k =1 17 = 2 2 i+ i=1 9 n n k2 + k (k + 1) = (k − 1)(k − 4) (b) k =5 Supplementary Exercises 7 19. (a) 252 If u = sec x, du = sec x tan xdx, sec2 x tan xdx = if u = tan x, du = sec2 xdx, (b) 20. 1 2 π /4 = 0 udu = u2 /2 + C2 = (tan2 x)/2 + C2 . x−1/3 1 2 tan2 x π /4 0 = 1 (1 − 0) = 1/2 2 x2/3 + 1dx; u = x2/3 + 1, du = 2 −1/3 x dx 3 u1/2 du = u3/2 + C = (x2/3 + 1)3/2 + C n n b 22. 1 (2 − 1) = 1/2 and 2 1 + x−2/3 dx = 3 2 udu = u2 /2 + C1 = (sec2 x)/2 + C1 ; They are equal only if sec2 x and tan2 x diﬀer by a constant, which is true. sec2 x 21. sec2 x tan xdx = b fk (x)dx = (a) a k =1 fk (x)dx k =1 a b (b) yes; substitute ck fk (x) for fk (x) in part (a), and then use a Theorem 7.5.4 x 23. (a) 1 fk (x)dx from a 1 d...
View Full Document

## This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online